Influence of MDR1 C1236T polymorphism on lopinavir plasma concentration and virological response in HIV-1-infected children - Bellusci, Carolina Paula (2013)
Background: Variability in MDR1 and PXR has been associated with differences in drug plasma levels and response to antiretroviral therapy. We investigated whether polymorphisms in MDR1 (T-129C, C1236T and C3435T) and PXR (C63396T) affect lopinavir plasma concentration and the virological or immunological response to HAART in HIV-1-infected children. Methods: Genotypes were identified in 100 blood donors and 38 HIV-1-infected children. All children received HAART with lopinavir boosted with ritonavir (LPV/r) at the time of LPV plasma level quantification, before (Ctrough) and between 1 and 2 h after (Cpost-dose) the administration of the next dose of drug. CD4+ T-cell counts and plasma viral load were analyzed before and after the initiation of LPV/r. Results: MDR1 1236T, MDR1 3435T and PXR 63396T alleles showed a frequency of ~ 50% while the MDR1 -129C allele only reached 5%. Children heterozygotes 1236CT showed a significantly lower LPV Cpost-dose than homozygotes 1236TT (median Cpost-dose = 3.04 μg/ml and 6.50 μg/ml, respectively; p = 0.016). Children heterozygotes 1236CT also had a lower decrease of viral load after 36 weeks of LPV/r exposure compared with homozygotes 1236CC (median viral load changes = − 0.50 log10 copies/ml and − 2.08 log10 copies/ml, respectively; p = 0.047). No effect on the immunological response was observed for polymorphisms of MDR1 or PXR. Conclusions: Our results suggest that the MDR1 C1236T SNP significantly reduces LPV plasma concentration affecting the virological response to HAART. Heterozygotes 1236CT might have an altered level of P-gp expression/activity in enterocytes and CD4+ T lymphocytes that limits the absorption of LPV leading to an impaired virological suppression.